Detection of Salmonella Spp. in Feed and Their Antibiotic Susceptibility for Alternative Therapy - Truong Huynh Anh Vu, Nguyen Ngoc Huu, Ha Dieu Ly, Nguyen Hoang Khue Tu (Journal of Applied Pharmaceutical Science, 2016)
In the study, about 695 samples comprising (fish powder: 320 samples, blood meal: 41 samples, bone meal: 123 samples), finished feed (pellets of pig feed: 213 samples) were collected and detected by polymerase chain reaction (PCR). Isolation prevalence in fish powder, blood meal, bone meal, finished feed was 23(7.19 %), 9 (21.95%), 48 (39.67%), 2 (0.94%) respectively. These Salmonella showed different antibiotic sensitivities to erythromycin, ampicillin, penicillin, ciprofloxacin. However, all these strains were inhibited with plantaricin produced by Lactobacillus plantarum PN05 isolated in Coryandrium sativum. Our findings highlighted a potential public health hazard and warned human the outbreaks of human salmonellosis with high resistance due to the consumption of contaminated feed and also suggested the prevention by plantaricin of Lactobacillus plantarum PN05.
Keywords: Salmonella, feed, detection, susceptibility.